The Effectiveness of a Training Program Based on Professional Reflection in Developing the Active Learning Skills among Science Teachers in the Capital City - Mutahar, Nadia Mohamed Ahmed; Al-Homaidi, Hazza Abdu (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the effectiveness of a training program based on professional reflection in developing the active learning skills of science teachers in the capital Sana'a. To achieve the objectives of the study, the quasi-experimental approach was used with one group (pre-post). The sample included (21) male and female science teachers; They were chosen intentionally. Also, a training program and a note card of active learning skills were prepared. The statistical analysis program SPSS was used to analyze the data, and the results showed: There is a statistically significant difference between the mean scores of the study sample teachers in the observation card in the application (pre and post) in favor of the post application. It was also found that the training program had a significant impact on developing active learning skills for science teachers. In light of the results, the study recommends several recommendations, the most important of which are: the need to include programs and activities for preparing teachers in the pre-preparatory stage with active learning skills and their educational applications, and the need to generalize the culture of professional reflection among teachers as one of the developments in the educational field.
Keywords: training program; professional reflection; active learning skills; science teachers; Sana'a City